VALIDITAS DAN PRAKTIKALITAS PENUNTUN PRAKTIKUM KIMIA BERBASIS GREEN CHEMISTRY UNTUK SEMESTER GENAP KELAS X IPA SMA - Susilawati Amdayani (Universitas Negeri Medan, 2021)
This study aims to develop a practical and valid green chemistry based practical guide for grade X SMA. This type of research is the development of research with 4D models consisting, 4D Models consist of four stages : define, design, develop and disseminate. Based on the results of the descriptive analysis of the data obtained, it can be stated that: 1) The green chemistry –based practicum guide developed is very valid, indicated by the kappa value obtained from the four validators 0,88 with a very high category; 2) The geen chemistry –based practicum guide developed is very practical, indicates bt the kappa value obtained from the practicality test of teachers and students is 0,89. And 0,81 with is very high categories From the results of validity and practicality test that have been done, it can be concluded that moduls have been developed are suitable for use as a learning resources.Keywords : Validity, Practicality, Green Chemistry